Social Media under the Skin: Facebook Use after Acute Stress Impairs Cortisol Recovery - Rus, Holly M.; Tiemensma, Jitske (Frontiers in Psychology, 2017)
Social media’s influence on stress remains largely unknown. Conflicting research suggests that Facebook use may both enhance and undermine psychosocial constructs related to well-being. Using novel experimental methods, this study examined the impact of social media use on stress recovery. Facebook users (n =92, 49 males, mean age 19.55 SD = 1.63) were randomly assigned to use their own Facebook profile or quietly read after experiencing an acute social stressor. All participants showed significant changes in subjective and physiological stress markers during recovery. Participants who used Facebook experienced greater sustained cortisol concentration (p < .05) when controlling for gender and emotional investment in the website compared to controls. Results suggest that social media use may delay or impair recovery after experiencing an acute social stressor. This novel study incorporated objective physiological markers with subjective psychosocial measures to show that Facebook use may negatively impact well-being.